FORMULASI PUPUK ORGANIK CAIR (POC) BERBAHAN LIMBAH KULIT BAWANG MERAH, KULIT JERUK, KULIT NANAS, DAN AIR CUCIAN BERAS DENGAN PENAMBAHAN EM4: Pembuatan Pupuk Organik Cair (POC) dari Kulit Bawang Merah, Kulit Jeruk, Kulit Nanas dan Air Cucian Beras dengan Penambahan EM4 - Mardi; Kurniawati, Desy; Rosalynna Stiadi, Della; Putri Ana, Aziza; Rara Bahri, Rayhani; Rahayu Ningsih, Sri (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
One solution to overcome the problem of household organic waste is to use technology to process it into liquid organic fertilizer (POC). POC is a solution that contains one or more essential nutrients that are easily absorbed by plants. The main ingredient for making quality POC comes from organic waste, especially wet organic material with high water content, such as fruit and vegetable waste. Several types of waste, such as onion peels, orange peels and pineapple peels, can be processed into POC by adding EM4 as an activator. This research aims to process fruit and vegetable waste into POC, improve skills in making it, and compare the effectiveness of POC with NPK fertilizer on the growth of chili plants. The process of making POC is carried out by mixing onion peel, orange peel and pineapple peel waste with water, rice washing water and brown sugar solution, then adding EM4. This mixture is fermented for seven days with daily stirring and ventilation. The research results show that the POC produced has good nutritional content and can be used as organic fertilizer.